Pengembangan Perangkat Pembelajaran Model Problem Based Learning dengan Soal Open-Ended Untuk Meningkatkan Kemampuan Berpikir Kreatif Matematik (PRISMA, Prosiding Seminar Nasional Matematika, 2016)
The aim of this research is to develope instructional equipments of mathematics Problem Based Learning model with Open-Ended Problem of equation and inequation system subject a valid,. The instructional equipments were valid based on the average score of validity, in which syllabus gained 3.88; lesson plan gained 3.94;supplementary books gained 3.78; students’ work sheets gained 3.82 and creative thinking competence gained 3.91 ; from maximum score 5.0. In addition students and teachers had positive responses. The instructional equipments were effective based on: (1) students’ creative thinking competence of mathematics reached 76; (2) students’ creative thinking competence of mathematics of experimental class was higher than control class; and (3) the average of creative thinking competence of mathematics improvement was on average by reaching 0,59. The improvement of creative thinking competence of mathematics of experimental class was higher than control class.